Hiroshi Sugimoto - Dioramas [... accompanies the Exhibition "Hiroshi Sugimoto: Still Life", Pace Gallery, May 9 - June 28, 2014, New York] - Sugimoto, Hiroshi 1948- (Pace Gallery, 2014)
'Hiroshi Sugimoto: Still Life' includes 'Polar Bear' (1976), his first photograph from the Diorama series, exhibited along with later works from the 1980s, 1990s, and, most recently 2012. Where many of the earlier silver gelatin prints present animals, a number of the 2012 photographs including Mixed Deciduous Forest and Olympic Rain Forest focus on natural landscapes. He has likened the record created by photography to a process of fossilization - the evidence of a moment suspended in time
This is the first in a series of publications on the artwork of Hiroshi Sugimoto. Future publ. will present 'Seascapes', 'Theatres', 'Architecture', and 'Lightning fields"
Keywords: Sugimoto, Hiroshi / 1948- / Exhibitions; Sugimoto, Hiroshi / 1948-; Sugimoto, Hiroshi -- 1948-; Geschichte 1980-2012; Still-life photography / Exhibitions; Diorama / Pictorial works / Exhibitions; Photographers / Japan; Diorama; Photographers; Still-life photography; Landschaft -- Motiv; Mensch -- Motiv; Tiere -- Motiv; Schwarzweißfotografie; Japan; Ausstellungskatalog -- Pace Gallery -- 09.05.2014-28.06.2014 -- New York, NY